Peran Humas Dalam Pembentukan Citra Fakultas Dakwah dan Ilmu Komunikasi IAIN Padangsidimpuan - Nurfitriani M. Siregar (IAIN Padangsidimpuan, 2019)
The purpose of this study is to assess an overview of the role of public relations in developing the image of the Da'wah and Communication Sciences faculty. To explore this, researchers conducted a qualitative descriptive study method using this approach as a way to analyze and discuss the data obtained. The role of public relations in each faculty in each tertiary institution is very important, because in every tertiary institution it requires the work of a publicist to assist the work program, and also public relations can maintain the image of an institution, so that an institution can be known and trusted by the public with public relations strategy. A PR is a bridge or the first door of an image that is formed in the community at a particular institution.Keyword: Public Relation, Imagery